The Prognostic Capacity of the Radiographic Assessment for Lung Edema Score in Patients With COVID-19 Acute Respiratory Distress Syndrome—An International Multicenter Observational Study - Valk, Christel M. A.; Zimatore, Claudio; Mazzinari, Guido; Pierrakos, Charalampos; Sivakorn, Chaisith; Dechsanga, Jutamas; Grasso, Salvatore; Beenen, Ludo; Bos, Lieuwe D. J.; Paulus, Frederique; Schultz, Marcus J.; Pisani, Luigi (Frontiers in Medicine, 2022)
Background The Radiographic Assessment for Lung Edema (RALE) score has an association with mortality in patients with acute respiratory distress syndrome (ARDS). It is uncertain whether the RALE score at start of invasive ventilation, or changes thereof in the next days, have prognostic capacities in patients with COVID–19 ARDS. Aims and objectives To determine the prognostic capacity of the RALE score for mortality and duration of invasive ventilation in patients with COVID–19 ARDS. Methods International multicenter observational study including consecutive patients from 6 ICUs. Trained observers scored the first available chest X–ray (CXR) obtained within 48 hours after start of invasive ventilation (‘baseline CXR’) and each CXRs thereafter up to day 14 (‘follow–up CXR’). The primary endpoint was mortality at day 90; secondary endpoint was the number of days free from the ventilator and alive at day 28 (VFD–28). Results A total 350 CXRs were scored in 139 patients with COVID–19 ARDS. The RALE score of the baseline CXR was high, and not different between survivors and non–survivors (33 [24–38] vs. 30 [25–38], P = 0.602). The RALE score of the baseline CXR had no association with mortality (HR, 1.24 [95%–CI 0.88–1.76]; P=0.222; area under the receiver operating characteristic curve (AUROC) 0.50 [0.40–0.60]). A change in the RALE score over the first 14 days of invasive ventilation, however, had an independent association with mortality (HR, 1.03 [95%–CI 1.01–1.05]; P<0.001). When the event of death was considered, there was no significant association between the RALE score of the baseline CXR and the probability of being liberated from the ventilator (HR 1.02 [95%–CI 0.99–1.04]; P=0.08). Conclusion In this cohort of patients with COVID–19 ARDS, with high RALE scores of the baseline CXR, the RALE score of the baseline CXR had no prognostic capacity, but an increase in the RALE score in the next days had an association with a higher mortality.